Prevalence, Incidence, and Recovery of Metabolic Dysfunction-associated Steatotic Liver Disease and Associations With Weight Loss and Lipid Reduction in a Chinese Community-based Cohort - Yurou Xu; Youyi Wang; Xiajing Yao; Qi Zhao; Bo Chen; Na Wang; Tiejun Zhang; Yonggen Jiang; Yiling Wu; Na He; Genming Zhao; Zhongxing Sun; et al. (Journal of Epidemiology)
Background: As the most common chronic liver disease worldwide, the natural history of metabolic dysfunction-associated steatotic liver disease (MASLD) in the general population is barely reported. Methods: The Shanghai Suburban Adult Cohort and Biobank study recruited 36,404 adults between 2016 and 2017, and followed up 25,085 participants between 2019 and 2023 in Songjiang District. A questionnaire survey was conducted using face-to-face interview, and physical examination and laboratory tests were conducted. MASLD was diagnosed using liver ultrasound and the cardiometabolic risk factors (CMRF). Results: A total of 36,122 and 21,831 participants met the criteria for baseline and follow-up analyses. The prevalence of MASLD at baseline was 36.8% overall, and 73.6% among those with a body mass index (BMI) over 28 kg/m2. After a median follow-up time of 4.26 years, the incidence density for MASLD was 8.4, and the recovery density was 11.4 per 100 person-years overall and was 20.0 and 8.4 per 100 person-years for those with baseline BMI over 28 kg/m2. Per 1 kg/m2 increase in baseline BMI was associated with a 15% increase in incidence (hazard ratio [HR] 1.15; 95% confidence interval [CI], 1.14–1.17) and an 8% decrease in recovery (HR 0.92; 95% CI, 0.90–0.93). From baseline to follow-up visit, participants who remained non-obese or remained normal cardiometabolic status always showed the lowest incidence and the highest recovery rate, followed by those with improved status. Conclusion: The prevalence and incidence of MASLD were high among Shanghai residents, and active recovery was also observed. Obesity was the most important risk factor, and weight loss and lipid level reduction were beneficial for preventing or reversing MASLD.